Pemeriksaan Bumbung Secara Visual di Bangunan Warisan Menggunakan Kaedah UAV Fotogrametri - Azari, Muhammad Firdaus; Adzmi, Nur Aqilah; Mohd Nizam, Nur Sufiah Izzaty; Kaamin, Masiri (Multidisciplinary Applied Research and Innovation, 2024)
Inspection of historic buildings is one of the important aspects of maintaining the structure to ensure it remains safe and preserved. The inspection method performed requires the inspector to climb a ladder and walk around the roof to identify damage. This method has invited risk and hazard to the inspector. This study aims to capture images of the roof and determine the type and extent of roof defects. The method used in conducting this study is the UAV photogrammetry technique using the Phantom 4 Pro UAV aircraft. The recorded images were processed and analyzed into Pix4DMapper. The results of the study were able to determine the type and location of roof defects. The overall defect level of the roof has also been calculated and determined and categorized as a moderate level based on the Condition Survey Protocol 1 Matrix (CSP1) evaluation concept.